Measurement of beam asymmetry for [pi]-[delta]++ photoproduction on the proton at E[gamma]=8.5 GeV; Physical Review C; Vol. 103, iss. 2 - Adhikari Sh. Shankar; Akondi C. S.; Ali A.; Amaryan M.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2021, 2021)
Title screen